PENGARUH PERSEPSI DAN KEPERCAYAAN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE PADA MAHASISWA STIEM BONGAYA - Baharuddin; Helmi Azizah Said; Indah Sari; Firdaus Omardi Syam; Tatun Anugerah; Putri Inayah Fatimah (LP2M IBK Nitro, 2022)
This study aims to examine the effect of risk perception, the effect of consumer trust and the effect of risk perception on purchasing decisions in the Shopee marketplace. In this study, it was carried out from June 2021 to September 2021. The sampling criteria had been determined, namely students of class 2020. Multiple linear regression is an analytical technique used in data processing and the tool to process the data is SPSS. Based on the results of the study, the results showed that the results of the analysis showed that the risk perception variable had no and insignificant effect on the purchasing decision variables in the Shopee marketplace, while the consumer confidence variable had a positive and significant effect on the purchasing decision variables in the Shopee marketplace, while the risk perception and consumer trust variables had a positive and significant effect. significant to the purchasing decision variables in the Shopee marketplace